(untitled) (Epidemiology, Biostatistics, and Public Health, 2025)
Background: The productivity loss attributable to the burden of diseases in different country contexts reflect the effectiveness of the context specific measures for population health development. So, this study provides insights into the productivity loss from the burden of diseases. Methods: Using country specific subnational level data, we have quantified the burden of diseases and the consequential lost productivity in two lower middle-income countries i.e., India and Kyrgyzstan; three upper middle-income countries i.e., Belarus, Kazakhstan and the Russian Federation; and one high income country, France. We have computed standard expected years of life lost (SEYLL) as the measure of disease burden, and quantified the present value of lost earnings (PVLE) using our 3P approach (population, participation and productivity). Results: Our subnational level analysis finds an overall declining trend of SEYLL across regions in each country except in Belarus from 2017 onwards, and in France. We also find that the cumulative percentage loss of PVLE per SEYLL mostly exceeds cumulative GDP per capita growth of the country during the study years. Conclusion: We have captured the value of earnings and quantified the avoidable loss for the society/country in different contexts and thus, this study demonstrates the potential contribution of population health development to the poverty alleviation programme in low – and middle – income countries.